SWOT, IFAS, EFAS, and SPACE Analysis of Competitive Advantage Enhancement Strategies for XYZ Bakery and Pastry UMKM in Facing Market Competition - Simorangkir, Natalie Zefanya; Ali, Hapzi (Siber International Journal of Education Technology (SIJET), 2025)
This study aims to evaluate the competitive advantage enhancement strategies implemented by the XYZ bakery and pastry UMKM amid the rapid growth of the industry in Indonesia, which has reached 7–10% per year. The increasing demand for practical and affordable products has led MSMEs in this sector to face increasingly intense market competition. This research uses a descriptive quantitative method that seeks to provide a systematic overview of the observed conditions and phenomena through numerical data, with the bakery and pastry UMKM as the research subject. The analysis results, using the SWOT, IFAS, EFAS, and SPACE approaches, indicate that the main strengths of the UMKM lie in product quality, innovation, and the use of social media as a promotional tool. However, the study also found that reliance on raw materials with fluctuating prices and suboptimal promotion efforts are the primary weaknesses of the MSME. An IFE score of 3.12 and an EFE score of 3.36 indicate that the implemented strategies have been effective in identifying and capitalizing on external market opportunities.